HLA ANTIGENS IN OCULAR TISSUES - David Abi‐Hanna; Denis Wakefield; Stanley Watkins (1988)
The eye is a common site for autoimmune inflammatory diseases, many of which are linked to HLA antigens. The role of these HLA phenotypes in the disease process is presently unknown. In view of the importance of HLA antigens to immune responses, a knowledge of the distribution of HLA antigens in ocular tissues may aid in our understanding of the role of these antigens in disease production or susceptibility. Apart from the cornea, the expression of HLA antigens in human ocular tissues has not been thoroughly investigated. In this study we examined the in vivo expression of HLA antigens in postmortem human eyes using immunohistochemical techniques. The majority of ocular cells were found not to express class I or class II HLA antigens, with the exception of the blood vessel endothelium, which was uniformly class I-positive. The significance of these results is discussed in relation to ocular immunity.